Flyback converter controlled by Arduino Uno - Khalid Badr Yas; Ahmed Rashid (Journal of Techniques)
This paper presented the design, simulation, and implantation a DC-DC step-up Flyback converter that regulates the output voltage to give the desired value 200 V 100 W and can be used in many application such as power supply. To give a regulated output voltage from the flyback converter, a feedback loop with Proportional-integral (PI) controller is used. A simulation of the flyback converter employed by MATLAB/Simulink under variation in the input voltage and load. Also, the practical implementation used Arduino Uno microcontroller to control the duty cycle through IR2110 driver at the change in the input voltage or resistive load. It gives better flexibility and a good response to the control system. The duty controller to create regulate output voltage by using voltage control mode.